Developing Changes in Our Reading of the World: A Pedagogical Proposal from Participative Action Research - Simona Trovato-Apollaro (Revista Electrónica Educare)
This paper presents the results of a research conducted with the group Women of Theater from Alajuelita. The research intended to answer the question of how to develop changes in our reading of the world. The goal of our study was the co-researchers’ raising awareness process leading them, from themselves, and by means of the abovementioned group, to read, interpret and reconstruct the environment in order to yield transformations in their lives and community. Through reflection, the process was investigated on the basis of the pedagogical practices of Augusto Boal´s Theater of Oppressed (Boal, 1980), as they were applied at the theater workshop together with the group of Women of Theather, at the library of the Educative Center Los Pinos in Alajuelita. The main elements of the implemented methodology respond to the Participative Action Research (PAR), where the dialectical participative relationship and the collective discussion make it possible the creation of learning. We used audio recordings as data collection tools, which were later systematized for their analysis. The paradigmatic position assumed was inspired by an approach related to the concept of complexity. This concept proposes a holistic view of reality, life, and, so, of pedagogy. According to such a view, we all are one, and the multiplicity is interconnected with each one of its parts, in continuous entropy. Under this approach, where the world is a system of systems interconnected among themselves, the main finding was to perceive pedagogy as an instrument for humanization, a magical object capable of valuing diversity and transforming our thoughts, life styles and values, and, in consequence, our reading of the world. We considered that such an important finding might help to develop changes in human beings and might inspire us to assume an ecological perspective towards relationships. Such a perspective might give rise to deep transformations in our social, political and economic structures.